Banning Childlike Sex Dolls : Sex Dolls that Appear as Children - Hendriks-Lundh, Monique (Nordisk Tidsskrift for Kriminalvidenskab, 2023)
Abstract This article examines legislative and political developments in Denmark and Norway from 2016 until 2022 on the topic of banning ‘child sex dolls’, i.e. ‘dolls that appear as/look like children’. In Norway, court cases are the focal point for the criminalisation/banning of child sex dolls and are therefore central to this article. A series of cases resulted in the Norwegian Supreme Court (finally) rendering a verdict in September 2019, where it decided that child sex dolls are to be considered forbidden as they imply a ‘sexualisation of children’, which is prohibited by Section 311 of the Norwegian Criminal Code. In Denmark, the focus lies in the political debate. One Danish political party suggested banning such dolls in 2016, but this was rejected by the Parliament. Since then, the debate has gone back and forth, primarily relying on advice from relevant organisations, i.a. Save the Children Denmark, until a bill banning the dolls was presented in November 2021. The article concludes that the scientific research is too scarce, i.e. that we have insufficient knowledge on the effect on the users of child sex dolls. We do not know whether continuously allowing the purchase and possession of child sex dolls leads to an increased number of sexual assaults against children – or a decline in that number. Experts argue that as long as we lack any solid evidence that the use of these dolls has a harmful effect it is heedless, and may even be risky, to ban them. The majority political opinion has changed over time, going from ‘we need more knowledge on the matter’ to ‘we need to protect the interests of the children, and the doubt of the harmful effect of the use of the dolls should be in the children’s benefit’. This change, however, has occurred in the absence of any scientific research to support it. Abstract Denne artikel redegør for udviklingen i Danmark og Norge fra 2016 til i dag (2022) på området for forbud mod ‘børnesexdukker’, eller ‘sexdukker der ser ud som/ligner børn’. For Norge er retssagerne fokuspunkt for kriminalisering af børnesexdukker, og således står de centralt i denne artikel. Retssagerne har ført til den første – og hidtil eneste – Højesteretsdom, der i september 2019 besluttede at børnesexdukker er forbudte, fordi de udgør en ‘seksualisering af børn’, der er omfattet af § 311 i den norske straffelov. For Danmark er fokus på den politiske debat. Et politisk parti foreslog i 2016 at dukkerne skulle forbydes, men dette blev nedstemt i Folketinget. Siden har debatten bølget frem og tilbage, primært baseret på organisationers vejledning på området, bl.a. Red Barnet, indtil et lovforslag, der forbyder dukkerne, blev præsenteret i november 2021. Det primære problem er, at der ikke er tilstrækkelig med videnskabelige undersøgelser, dvs. ikke nok viden, om effekten på de personer, der anvender børnesexdukker. Vi ved ikke om fortsat tilladelse til køb og besiddelse af børnesexdukker fører til et øget antal af seksuelle overgreb mod børn – eller et fald i det tal. Eksperternes mening er, at så længe vi ikke ved, om der er en skadelig effekt af brugen af disse dukker, er det unødvendigt, og måske endda risikabelt, at forbyde dem. Hovedparten af politikernes mening er skiftet over tiden fra ‘vi bliver nødt til at opnå mere viden på området’ til ‘vi må beskytte børnenes interesser, og tvivlen angående den skadelige effekt af brugen af dukkerne skal veje til børnenes fordel’ – uden, dog, at basere dette på videnskabelige undersøgelser.